Ethics committees for clinical experimentation at international level with a focus on Italy - Naureen, Zakira; Beccari, Tommaso; Marks, Robert S.; Brown, Richard; Lorusso, Lorenzo; Pheby, Derek; Miertus, Stanislav; Herbst, Karen L.; Stuppia, Liborio; Henehan, Gary; Falsini, Benedetto; Lumer, Ludovica; et al. (Acta Biomedica Atenei Parmensis, 2020)
Guiding legislation and associated bureaucracy for the ethical review of clinical trials observational studies and food related research play an important role in the competitiveness of a nation in the face of tough global competition to attract sponsors and investigators. This is of particular relevance in the case of multicentre trials and multidisciplinary research. Accordingly, in this report we tried to gather in-depth knowledge of the current role and practices of ethics committees nationwide in both clinical and research settings. This mini-review aims to describe the formulation and organization of ethical committees in Italy in order to provide a focus for deliberations on ethical issues in medical and scientific research in line with human rights, as set out in the European Union charter. Furthermore, we evaluated the impact of an institution’s ethical committee intervention on reducing the time required to obtain an opinion from Research Ethics Committees by guiding investigators in addressing ethical issues in their proposed studies.